Effect of long-term use of kinesiotape on hallux valgus angle: A double-blinded randomized controlled trial - Mohamed M. Ahmed; Mohammed Qasheesh; Mahmoud Fathi Gomaa Moustafa; Nader I. ELsayed ELsayed; Ahmed A E Abdallah; Sahar M. Abdelmutilibe; Ahmed Youssef (Universidad de Murcia, 2023)
Article accepted. The article will be published here soon. Pending final quality checks.